Evaluation of frost resistance in oat - Rizza, Fulvia; Pagani, Donata; Reggiani, Fabio; Cattivelli, Luigi (MTT, 2004)
Resistance to biotic and abiotic stress is a crucial aspect for cultivar adaptation to agriculture environments. Among winter cereals, oat is the most frost sensitive and its insufficient level of winterhardiness is the main factor limiting sowing of winter oat in Northern Italy and Central Europe. Frost resistance, the most important component of winterhardiness, is an inducible process promoted by cold exposure and associated with a number of biochemical and molecular changes. We employed field tests and physiological parameters in a set of cultivars released during the last 40 years to explore the genetic variability in frost resistance and identify resistant genotypes. Plants were hardened at +3/+1°C and exposed to freezing temperatures. The efficiency of the excitation capture by open Photosystyem II (PSII) reaction centres was evaluated after freezing, through the chlorophyll fluorescence parameter Fv/Fm, according to Rizza et al. (2001). Different hardening length and pre-hardening temperature (+12/+7°C) were also employed to investigate if a higher level of resistance is associated with the ability to induce early hardening. This capacity is of advantage under field conditions, where temperature falls progressively, because it enables resistant plants to prepare for cold before the susceptible ones. Some significant molecular traits associated to frost resistance such as the accumulation of cor14 (Cattivelli et al., 1995) were also investigated on selected cultivars. Fv/Fm analysis appears as an attractive test being rapid, non invasive and able to monitor a trait related to a crucial mechanism of the resistance acquisition. Significant differences in frost resistance were detected within winter cultivars. The most resistant showed a behaviour similar to that of winter barley, suggesting that it should be possible to improve the resistance of winter oat to a level similar to that of winter barley. Rizza, F. Pagani, D. Cattivelli, C. Stanca, A.M. 2001. Plant Breeding 120: 389-396; Cattivelli, L. Crosatti, C. Rizza, F. 1995 Journal of Genetics & Breeding 49:333-338.
Keywords: Ka; Avena sativa; frost tolerance; cold hardening; chlorophyll fluorescence; Photosystem II; cor genes